El Excentrico, 1967-05-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
May 05, 1967 [5 de mayo de 1967], No volume or Issue number. Cover has a portrait of a model named Patrica, who has won the title of Queen of the Cinco of May Fiesta. The headline reads, "Reina Del 5 De Mayo." (transl: Queen of the 5 of May).